Application of grey systems theory in the analysis of relationships between family enterprise communication and their market attitude - Majchrzak, Joanna; Więcek-Janka, Ewa (Zastosowanie Teorii Szarych Systemów w analizie relacji między komunikacją a postawą rynkową przedsiębiorstw rodzinnych, 2019)
In this paper, the concept of analysing the relationship between family enterprise internal and external communication and the types of its behaviour in market activities is discussed. Family enterprise communication is the characterized and the use of the Internet for marketing communication is presented. Digital communication requires the new competences enabling to combine knowledge of marketing functions and knowledge of instruments and technologies of information communication. The sequence of specified operations, based on Grey Incidence Analysis, for identifying relationships between the degree of concentration on internal or external communication and family enterprise market attitude is designed. The proposed method is tested on twenty family enterprises and the efficacy of the calculation operations is confirmed. The findings facilitate highlighting how the degree of concentration on internal and external communication impact the family enterprise’s market position
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 3 (53), s. 30-48
Keywords: marketing communication; family business; uncertain system; grey relation analysis; komunikacja marketingowa; przedsiębiorstwa rodzinne; systemy niepewne; analiza szarych relacji